Colonialism, Resistance, and Environmental Issues in James Cameron’s Avatar (2009) - Yosua Tunas Wicaksono; Daniel Ginting; F.X. Dono Sunardi (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Avatar has revolutionized the film industry. James Cameron introduced a new level of immersive visual storytelling that captivated audiences worldwide. While some previous studies on Avatar have highlighted some important research findings, they seem to leave Avatar’s themes understudied.